Fertility Intentions and Their Realisation: Insights from the Polish Generations and Gender Survey - Zuzanna Brzozowska; Monika Mynarska (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
The aim of the paper is to investigate the link between fertility intentions and outcomes in Poland. Previous studies detected large differences between countries in the extent to which childbearing plans are realised. Specifically, failure to realise an intention to become a parent was found to be particularly common in the post-socialist countries. We use the two waves of the Polish Generations and Gender Survey, conducted in years 2010/2011 and 2014/2015, to verify whether the same can be observed for Poland. We find that approximately 35% of respondents, who at wave 1 intended to have a child in the next three years, actually got one by wave 2. The results are in line with those obtained in other postsocialist countries. For respondents who did not get a child between wave 1 and 2, we analyse the stability of their fertility plans. Both realisation and stability of fertility intentions vary markedly by gender and parity.
Keywords: 300; Fertility intentions; realization and stability of fertility intentions; Poland